1989
DOI: 10.1128/aac.33.12.2149
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of human immunodeficiency virus type 1 replication by the (-) but not the (+) enantiomer of gossypol

Abstract: The (-) enantiomer of gossypol but not the (+) enantiomer had good antiviral activity in peripheral blood mononuclear cells against human immunodeficiency virus type 1 at a concentration more than 20-fold lower than that required for cytotoxicity; however, in H9 cells the (-) enantiomer, although more potent as an antiviral agent, was more cytotoxic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 29 publications
0
51
0
Order By: Relevance
“…It is not clear whether the inhibition of HIV-1 reverse transcriptase by gossypol is the primary mechanism of action. Lin et al (1989) have synthesized analogs of gossypol for potential antiviral activity against HIV-1.…”
Section: Antivirus Propertiesmentioning
confidence: 99%
“…It is not clear whether the inhibition of HIV-1 reverse transcriptase by gossypol is the primary mechanism of action. Lin et al (1989) have synthesized analogs of gossypol for potential antiviral activity against HIV-1.…”
Section: Antivirus Propertiesmentioning
confidence: 99%
“…16 Their high activity against viruses presents a new possibility to use derivatives of gossypol in the development of new kinds of antiviral drugs. [17][18][19][20] Moreover, an earlier investigation indicated that gossypol analogues may have therapeutic potential against human breast cancer. 21 The addition of amines to cottonseed causes lower toxicity of animal fodder.…”
Section: Introductionmentioning
confidence: 98%
“…14 The presence of gossypol derivatives in the database search results posed an interesting question. The parent gossypol compound was reported in 1989 as an anti-HIV agent, 19 however, it was stated that it was unlikely to be primarily a reverse transcriptase inhibitor, although no data was presented for the effects of gossypol in a reverse transcriptase assay. In a later article (1995), 20 the effects of gossylic iminolactone (GIL) were compared to those of AZT to ascertain whether they have different targets.…”
Section: Figure 4: An Example Of An Adam (Arenediarylmethane) Structumentioning
confidence: 99%